The hard times guide to retirement security : practical strategies for money, work, and living - Miller, Mark (Bloomberg., 2010)
"The need to build retirement security has never been greater. But one of the main obstacles is the current concept of retirement--the idea that people should stop working in their early sixties and take it easy. The number of years that you'll have to fund after you stop working is one of the most important variables affecting retirement security."--Page 2.